“Mutual Assistance” Culture to Maintain Corporate Sustainability - Karsam Karsam; Erfan Erfiansyah; Inugrah Ratia Pratiwi; Hendriyana Hendriyana; Siti Kodariah (Journal of Accounting and Investment, 2022)
Research aims: This article aims to demonstrate that corporate sustainability will be more balanced and sustainable if it is based on the philosophy of "mutual assistance (gotong royong) culture." (Mutual assistance synergizes to maintain and improve).Design/Methodology/Approach: The research method used was a qualitative method with a phenomenological approach, i.e., a constructivist or naturalistic approach.Research findings: This study disclosed that corporate sustainability would continue to be maintained with the awareness of every company member to work together to sustain, maintain, and improve performance. The application of the corporate sustainability concept must also be based on the spirit of building, maintaining, and improving all aspects of business activities (without giving up). In addition, the company's synergy with the mutual assistance culture will bring the company's safety to a continuous and lasting one.Theoretical contribution/Originality: Implementing corporate sustainability based on mutual assistance culture will increase the company’s existence and sustainability. In this case, managers can focus on corporate sustainability while still paying attention to the mutual assistance culture of all organization/company members.Practitioner/Policy implication: The mutual assistance culture can be used as a guide/companion for companies in implementing the business sustainability concept.Research limitation/Implication: This article offers the Javanese philosophy concept of mutual assistance culture in maintaining business sustainability.